Influence of intercalation-exfoliation-reduction technique towards the physico-chemical of VPO catalysts - Wong, Yee Ching; Yap, Taufiq Yun Hin (Hindawi Publishing Corporation, 2013)
Four VPO catalysts were synthesized through intercalation and exfoliation in various alcohols and subsequent reduction of the exfoliated VOPO4 sheets with various alcohols to produce VOHPO40.5H2O. The resulting VOHPO40.5H2O that undergoes the intercalation-exfoliation-reduction (IER) process will be further activated into VPO catalysts, and addition of 1 mole Bi(NO3)35H2O in the first stage of this experiment has also being investigated. The synthesized materials were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), transmission electron microscope (TEM), and temperature-programmed reduction (TPR) in H2. Catalytic evaluation of the IER-treated and Bi-doped VPO catalysts was also studied on microreactor. The VPO catalyst produced through IER using 2-butanol and ethanol with addition of Bi, IERC(2Bu-Et)RBi1, gave the highest MA selectivity due to reactive O 2- species released from the additional crystalline V 5+ phase formed by doping 1 bismuth as promoter (O 2-V 5+ pair) at relative lower temperature. Nevertheless, the VPO catalyst produced through IER using isobutanol, IERC(isoBu), gave the highest activity due to high amount of reactive O - species released from V 4+ phase (O - V 4+ pair) whereby the IERC(isoBu) catalyst synthesized consists of high percentage of V 4+ (93).